Caracteres limnológicos de algunos lagos eutróficos de embalse de la región central de Argentina - Bonetto, Argentino A.; Di Persia, Danilo H.; Maglianesi, Roque; Corigliano, María del C. (Ecosur, 2025)
The limnological knowledge of man-made lakes in Neo tropical America results extremely poor, what means a particularly regrettable déficit facing the accelerate increasing number and magnitude of such impoundments. This paper deais with the results of limnological studies on three man-made lakes of the province of Córdoba (Argentina), with diverse characteristics and degrees of eutrophy, developed through sampling and fíeld works made with a roughly seasonal periodicity. There have been considered the main physical and Chemical features of the waters, including those cor respon ding to the afñuents and effluents of each lake , the phytoplancton, chlorophyll contení and primary production; the stmcture, density, distribution, specifíc diversity and biomass of the zooplancton; the s truc ture, distribution and biomass of benthos (specially conceming with the Oligochaeta), and the fish populations, as well as the fishery m anage ment in reía don to the process and degrees of eutrophication.